2014
DOI: 10.1007/s12264-013-1400-5
|View full text |Cite
|
Sign up to set email alerts
|

Awareness is essential for differential delay eyeblink conditioning with soft-tone but not loud-tone conditioned stimuli

Abstract: The role of awareness in differential delay eyeblink conditioning (DEC) remains controversial. Here, we investigated the involvement of awareness in differential DEC with a soft or a loud tone as the conditioned stimulus (CS). In the experiment, 36 participants were trained in differential DEC with a soft tone (60 dB) or a loud tone (85 dB) as the CS, paired with a corneal air-puff as the unconditioned stimulus (US). After conditioning, awareness of the relationship between the CS and the US was assessed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(85 reference statements)
0
2
0
1
Order By: Relevance
“…Therefore, while trace conditioning appears to critically depend on awareness, data regarding the role of awareness in delay conditioning appears more equivocal. Interestingly, when unaware subjects were conditioned with a soft CS they poorly learned differential delay eyeblink conditioning compared to aware subjects, but unaware subjects conditioned with a loud CS showed no difference in conditioning to similarly conditioned aware individuals (Huang et al, 2014). This finding speaks to the importance of methodological and procedural factors that likely play a key part in unraveling the role of awareness in delay conditioning.…”
Section: Declarative Memory and Trace Conditioningmentioning
confidence: 99%
“…Therefore, while trace conditioning appears to critically depend on awareness, data regarding the role of awareness in delay conditioning appears more equivocal. Interestingly, when unaware subjects were conditioned with a soft CS they poorly learned differential delay eyeblink conditioning compared to aware subjects, but unaware subjects conditioned with a loud CS showed no difference in conditioning to similarly conditioned aware individuals (Huang et al, 2014). This finding speaks to the importance of methodological and procedural factors that likely play a key part in unraveling the role of awareness in delay conditioning.…”
Section: Declarative Memory and Trace Conditioningmentioning
confidence: 99%
“…Por otra parte, quizás la principal dificultad es la demostración de que un número sustancial de participantes, quienes, además de estar conscientes de las contingencias (Huang et al, 2014;Knuttinen, Power, Preston, & Disterhoft, 2001;Lovibond et al, 2011;Lovibond & Shanks, 2002;Weidemann, Best, Lee, & Lovibond, 2013;Weidemann & Antees, 2012), emiten las llamadas respuestas voluntarias (RV) (Goodrich, 1966;Gormezano, 1965;Rasmussen & Jirenhed, 2017;Spence & Ross, 1959). Específicamente, Spence y Ross (1959) mostraron que algunos sujetos dan una alta incidencia de respuestas que se caracterizan por un cierre fuerte, suave del párpado, con el ojo cerrado hasta después de que el soplo de aire es recibido.…”
Section: Introductionunclassified
“…The effects of CS discriminability on awareness and conditioning have been reported in fear conditioning studies (Knight et al 2003;Schultz and Helmstetter 2010;Singh et al 2013) but have not been directly investigated using EBC. While the majority of differential delay EBC studies used two distinct CSs (tone and white noise) that were fairly easy to discriminate, several have used two pure tones of varying frequencies as CSs and measured awareness (Ross and Nelson 1973;Nelson and Ross 1974;Huang et al 2014). These studies found that awareness was needed for differential delay EBC although another study reports contradictory findings (Smith et al 2005).…”
mentioning
confidence: 99%